Análisis crítico del Derecho Comparado. Entrevista a Tom Ginsburg - Bendezú Medina, Samuel H. (Pontificia Universidad Católica del Perú, 2016)
In this interview, the professor Tom Ginsburg addresses Comparative Law, the conditions for its study, its influence in capitalism, as well as his comparative studies over the constitutions, especially, of Latin American ones. He also addresses the conceptions that societies have about the relationship between Law and society, the moment of the creation of a Constitution, the factors involved in it and the perception of the judges and their decisions.

En la presente entrevista, el profesor Tom Ginsburg comenta acerca del Derecho Comparado, de las condiciones para su estudio, de su influencia en el capitalismo, así como sus estudios comparados sobre las constituciones, en especial, de las latinoamericanas. También comenta las concepciones que las sociedades tienen acerca de la relación entre el Derecho y la sociedad, el momento de la creación de una Constitución, los factores involucrados en ella y, sobre la percepción de los jueces y sus decisiones.
Critical analysis of Comparative Law. Interview with Tom Ginsburg
Keywords: Comparative Law; Constitutions; Juridical Realism; Law And Society; Judicial Decision; Derecho comparado; Constituciones; Realismo Jurídico; Derecho y Sociedad; Decisión Judicial; https://purl.org/pe-repo/ocde/ford#5.05.00